2021
DOI: 10.1093/jisesa/ieaa148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Agro-industrial Byproducts on Bioconversion, Chemical Composition, in vitro Digestibility, and Microbiota of the Black Soldier Fly (Diptera: Stratiomyidae) Larvae

Abstract: The interest in using byproducts from agro-food industries as a rearing substrate for insects is increasing rapidly. We investigated the influence of byproducts of vegetal origin (okara—a byproduct of soy milk production, maize distillers with solubles, brewer’s grains), used as rearing diet for black soldier fly larvae (BSFL), on the following parameters: biomass production, substrate reduction (SR), nutritional profile and in vitro digestibility, and larval gut microbiota. Hen diet was used as a control subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 54 publications
1
37
0
Order By: Relevance
“…Even though only a minor fraction of a community unveiled by sequencing methods is culturable (Alain and Querellou, 2009;Prakash et al, 2013), the bacterial profile found within these culture-independent studies is to some extent comparable to that found via our approach. Overall, these studies reported that the most representative phyla are the Proteobacteria, the Firmicutes, the Bacteroidetes and to a lesser extent the Actinobacteria (Jeon et al, 2011;Zheng et al, 2013;Wynants et al, 2018;Bruno et al, 2019b;Jiang et al, 2019;Zhan et al, 2019;Ao et al, 2020;Klammsteiner et al, 2020;Liu et al, 2020Liu et al, , 2021Raimondi et al, 2020;Shelomi et al, 2020;Galassi et al, 2021;Wu et al, 2021). In our collection, these four phyla are also represented: the Proteobacteria (66.3%), the Firmicutes (30.2%), the Bacteroidetes (2.9%) and the Actinobacteria (0.6%).…”
Section: Representativeness Of the Collectionmentioning
confidence: 54%
See 1 more Smart Citation
“…Even though only a minor fraction of a community unveiled by sequencing methods is culturable (Alain and Querellou, 2009;Prakash et al, 2013), the bacterial profile found within these culture-independent studies is to some extent comparable to that found via our approach. Overall, these studies reported that the most representative phyla are the Proteobacteria, the Firmicutes, the Bacteroidetes and to a lesser extent the Actinobacteria (Jeon et al, 2011;Zheng et al, 2013;Wynants et al, 2018;Bruno et al, 2019b;Jiang et al, 2019;Zhan et al, 2019;Ao et al, 2020;Klammsteiner et al, 2020;Liu et al, 2020Liu et al, , 2021Raimondi et al, 2020;Shelomi et al, 2020;Galassi et al, 2021;Wu et al, 2021). In our collection, these four phyla are also represented: the Proteobacteria (66.3%), the Firmicutes (30.2%), the Bacteroidetes (2.9%) and the Actinobacteria (0.6%).…”
Section: Representativeness Of the Collectionmentioning
confidence: 54%
“…Soluble carbon sources, such as soluble starch, were not included in the study, since BSFL can produce amylase enzymes when fed substrates containing starch (Kim et al, 2011;Bonelli et al, 2019;Bruno et al, 2019a). Since bacteria that are more adapted to digest a specific compound can be expected to have a higher fitness on specific diets (De Smet et al, 2018;Galassi et al, 2021), we hypothesize that these bacteria will be more abundant in the community and concomitantly are more likely to be isolated. We selected five fiber types to enrich (each individually) substrates with.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, larvae obtained in this work contained linoleic acid (4.44-12.7%) levels comparable to larvae reared on chicken feed (14.7%), but lower than those reared on okara (28.4%), maize distillers (24.3%) fish offal (25.1%), brown algae (24%) or hemp seeds (26%) [11,31,39,40]. Oleic or linoleic were reported to be derived from biosynthesis pathways and diet accumulation, unlike lauric acid (exclusively synthesized) [32].…”
Section: Hermetia Illucensmentioning
confidence: 60%
“…Spranghers [30] suggested that H. illucens synthesizes lauric acid from carbohydrates in the substrate. In a recent study, it was found that rearing H. illucens on okara resulted in a drastic reduction in lauric acid (17.6% of total fatty acids), because okara has poor levels of carbohydrates (starch and sugars) required for lauric acid synthesis [31]. In fact, carbohydrates are a source of acetyl-CoA, which is necessary for the biosynthesis of fatty acids.…”
Section: Hermetia Illucensmentioning
confidence: 99%
“…Scrofimicrobium is a new genus of the Actinomycetaceae family, which is closely related to Actinomyces and only described so far by Wylensek et al (2020) based on isolates from the pig gut. Actinomyces has been found before in BSFL gut studies (Ao et al, 2020;Galassi et al, 2021;Gold et al, 2021). Based on this meta-analysis, members of the above mentioned bacterial genera can be clearly considered as core genera of the BSFL gut community.…”
Section: Core Bacterial Genera Reoccur In Bsfl Gut Samples Despite In...mentioning
confidence: 80%